Okul Kültürü İle Öğrencilerin Şiddete Başvurma Davranışları Arasındaki İlişkiler - Demirtaş, Zülfü; Ersözlü, Alpay (Tokat Gaziosmanpaşa Üniversitesi, 2007)
The aim of the study was examined the relationships between school cultures and students’ behavior intended for violence. The sample of the study consisted of 11 primary school in center of Tokat on the 2007-2008 education year. The school culture scale was performed teachers and administrators in this schools for determining school culture levels. The relationships between students’ behavior intended for violence which were entered in official recordings in the midst of 2004-2007 years and school cultures were tested with statistical technics. According to the findings, cooperative culture was dominant in the schools. Administrators and teachers had been worked coopreration towards educaitonal purposes were realized. Female teachers were considered school cultures more cooperative than male teachers. There was a meaningful difference among the teachers’perceptions towards school cultures according to their branchs. Primary school teachers and the other teachers were perceived distinctly from each other. There was a negative meaningful relationship in the middle level between school cultures and students’ behavior intended for violence. In the other words, whenever school culture developed the students’ behavior intended for violence was diminishable

Araştırmanın amacı okul kültürleri ile öğrencilerin şiddete başvurma davranışları arasındaki ilişkileri araştırmaktır. Araştırma 2007-2008 öğretim yılında Tokat ili Merkez ilçedeki 11 ilköğretim okulunda yürütülmüştür. Okul kültürlerinin doğasını belirlemek için Okul Kültürü Ölçeği okullarda bulunan yönetici ve öğretmenlere uygulanmıştır. Bu okullara mensup öğrencilerden 2004-2007 yılları arasında resmi kayıtlara geçen şiddete başvurma davranışları ile okul kültürü verileri arasındaki ilişkiler istatiksel yöntemlerle sınanmıştır. Bulgulara göre, okullarda işbirlikçi bir kültür egemendir. Yöneticiler ve öğretmenler eğitimsel amaçları gerçekleştirme doğrultusunda işbirliği içerisinde çalışmaktadırlar. Kadın öğretmenler erkek öğretmenlere göre okul kültürlerini daha fazla işbirlikçi olarak görmektedirler. Öğretmenlerin branşlarına göre okul kültürüne yönelik algıları arasında farklılıklar vardır. Sınıf öğretmenleri ile branş öğretmenleri okul kültürlerini farklı algılamaktadırlar. Okul kültürleri ile öğrencilerin şiddete başvurma davranışları arasında negatif yönde orta düzeyde anlamlı bir ilişki vardır. Yani okul kültürü geliştikçe öğrencilerin şiddete yönelik davranışlarında azalma görülmektedir